The Influence of Work Discipline and Job Satisfaction on Employee Performance of Class II B Jombang Correctional Institution: (Case Study on Administrative Employees) - Sukasa, Adilla; Prasetyo, Deni Widyo (CV. Proaksara Global Transeduka, 2024)
The importance of work discipline and job satisfaction in improving employee performance at the Class II B Jombang Correctional Institution, especially administrative employees. This study aims to identify and analyze the effect of work discipline and job satisfaction on employee performance at the institution. The research method used is a quantitative approach with explanatory research type. The study population consisted of 48 administrative employees at the Class II B Jombang Correctional Institution, with a saturated sample technique involving the entire population. Data were collected through a questionnaire with a 5-point Likert scale and analyzed using multiple linear regression with the help of SPSS software version 25. The results showed that work discipline and job satisfaction have a positive and significant influence on employee performance. Good work discipline and high job satisfaction significantly improve employee performance at Class II B Jombang Correctional Institution. The Adjusted R Square value of 0.256 indicates that the work discipline and job satisfaction variables together explain 25.6% of the variability in employee performance, while the rest is influenced by other factors outside this study.